2004
DOI: 10.1128/jvi.78.21.11807-11815.2004
|View full text |Cite
|
Sign up to set email alerts
|

Coevolution of RANTES Sensitivity and Mode of CCR5 Receptor Use by Human Immunodeficiency Virus Type 1 of the R5 Phenotype

Abstract: The evolution of human immunodeficiency virus type 1 (HIV-1) coreceptor use has been described as the acquisition of CXCR4 use linked to accelerated disease progression. However, CXCR4-using virus can be isolated only from approximately one-half of individuals with progressive HIV-1 disease. The other half continue to yield only CCR5-using viruses (R5 phenotype) throughout the course of disease. In the present work, the use of receptor chimeras between CCR5 and CXCR4 allowed us to study the evolution of HIV-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
96
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(103 citation statements)
references
References 67 publications
5
96
1
1
Order By: Relevance
“…The more promiscuous utilization of CCR5 conformations by CC Envs may reflect selection pressures in chronic infection where neutralizing antibodies are abundant and certain populations of CD4 ϩ CCR5 ϩ cells have been diminished or otherwise altered by viral cytopathicity. Earlier studies have shown that R5 viruses can become increasingly resistant to entry inhibitors over time, consistent with alterations in CCR5 use (73)(74)(75). More promiscuous utilization of CCR5 could expand viral tropism under these conditions, in contrast to de novo infection of naïve hosts where virus infection of a more homogeneous population of CD4 ϩ CCR5 ϩ cells could be favored.…”
Section: Discussionmentioning
confidence: 85%
“…The more promiscuous utilization of CCR5 conformations by CC Envs may reflect selection pressures in chronic infection where neutralizing antibodies are abundant and certain populations of CD4 ϩ CCR5 ϩ cells have been diminished or otherwise altered by viral cytopathicity. Earlier studies have shown that R5 viruses can become increasingly resistant to entry inhibitors over time, consistent with alterations in CCR5 use (73)(74)(75). More promiscuous utilization of CCR5 could expand viral tropism under these conditions, in contrast to de novo infection of naïve hosts where virus infection of a more homogeneous population of CD4 ϩ CCR5 ϩ cells could be favored.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, in vivo, the CCR5 receptor may have different conformations in the presence of chemokines. It has been shown that envelopes from the late phase of infection compared to the variants from the chronic stage of disease display an increased ability to bind a broad range of chimeric CCR5 receptors (30). Therefore, an ability to bind different structural forms of the CCR5 receptor may explain the increased CCR5 usage among chronic-stage variants compared to the earlyinfection isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with more advanced disease have a greater likelihood of harboring X4-utilizing viruses [52][53][54] and have R5-tropic viruses with reduced sensitivity to RANTES and the CCR5 antagonists TAK779 and AD101 compared with patients at earlier disease stages. [55][56][57][58] As a consequence, these patients may fail R5 antagonist therapy via either outgrowth of minor preexisting X4-utilizing populations or the continued use of CCR5 in the presence of drug. In patients treated earlier during the course of infection, who have lower levels of circulating X4-tropic viral isolates, continued use of R5 may be a more common resistance pathway.…”
Section: Discussionmentioning
confidence: 99%